Studies in preferences for public goods in Ireland - Delaney, Liam (Trinity College (Dublin, Ireland). Department of Economics, 2005)
This dissertation is based on two studies conducted in 2002 and 2004 analysing preferences for non-marketed activity in Ireland. The first study applies the contingent valuation method (CVM) to Irish public service broadcasting. The second study examines public support for income maintenance schemes in Ireland and support for general policies of income redistribution. The studies have a number of things in common. Both public broadcasting and income maintenance are nationwide nonmarketed goods for which there is no adequate marketed measure of preferences. Both are familiar and politicised markets requiring subtlety in survey design and administration to attain meaningful answers. Both studies offer interesting case studies in the survey approach to political economy as well as offering more general insights in to the techniques of preference elicitation.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin